Implementation of Environmental Care Character Education at SD Muhammadiyah 9 Tanggulangin during the Covid-19 Pandemic - Risa Hayati; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of writing this research is to find out how the implementation of environmental care character education in SD Muhammadiyah 9 Tanggulangin during the covid-19 pandemic. The research method used is descriptive qualitative research. That is a study that understands social problems that exist in society by analyzing and presenting them using words to create a picture of the problems that exist in society obtained from sources. This study explains what the implementation of environmental care character education is like in SD Muhammadiyah 9 Resolve. One of the problems that often occurs is that students often throw garbage carelessly which results in damage to environmental sustainability in schools. In this time of the COVID-19 pandemic, schools conducting full online learning will certainly affect the implementation of environmental care character education which is usually always applied in schools. Teachers must also be more creative in conducting online learning by inserting environmental care character education so that students understand more about caring for the environment. The implementation of environmental care is applied by the way teachers can conduct learning using the e-learning method, namely learning that utilizes information and communication technology as well as working with parents to always monitor and assist the development of students in implementation. Environmental care character education. Online learning is carried out through a cellphone or laptop that is connected to an internet network connection. The learning process uses plates from, zoom, google meet and whatsapp groups. Learning that is applied to the implementation of environmental care character education, the teacher will provide material first, students learn the material that has been given by the teacher, before holding learning through zoom, then they are given LKPD to do with the help of parents which contains the planting of environmental care characters.